Adesão de cuidadores de indivíduos com TEA à intervenção baseada em ABA (Applied Behavior Analysis): uma revisão dos modelos de orientação e treino parental propostos na literatura analítico comportamental - Stadler, Jéssica Cristina (2023)
For decades, Behavior Analysis has been conducting research and presenting robust data that demonstrate the effectiveness of interventions based on Applied Behavior Analysis (ABA) for people with Autistic Spectrum Disorder (ASD) implemented by caregivers. However, these caregivers' adherence to behavioral treatment is significantly lower than adherence to other treatments, for example, medication. The objective of this work is to review parental guidance and training models proposed in the behavioralanalytic literature, analyzing whether and in what way strategies to favor the adherence of caregivers of individuals with ASD to ABA-based interventions have been implemented, and whether researchers have correlated caregivers' adherence or nonadherence to the effects of implemented strategies and interventions. The search for articles was carried out in four databases (PubMed, PsycINFO, Scopus and Portal de Periódicos da CAPES), by combining search words on “parental training”, “behavioral intervention”, “behavior analysis” and “autism spectrum disorder”. From the application of inclusion and exclusion criteria, 29 researches were selected. The results showed that, for the most part, parental training programs aim to both maximize skills and minimize children's behavior, through individual sessions, which are usually weekly and last for an average of up to three months, where teaching strategies are presented that involve both orientation and direct training. Mothers are usually the main caregivers who participate in training, and fathers have a more discreet participation. In addition, the results of this review also showed that: researchers, for the most part, have referred to parental adherence, but without using indexed terms for such (such as “adherence” or “adhesion”); the most used strategies to favor adherence are the selection of intervention objectives validated or suggested by caregivers, or specific to their children, and the teaching of concepts on which the procedures taught to caregivers are based; most surveys collect data about the caregivers' understanding of the concepts and procedures taught, and also about the parents' acceptance of the training objectives, procedures and results; and behavioral-analytical researchers have established a relationship, albeit discreetly, between adherence rates and the strategies and interventions implemented during parental training. It is hoped that this work will allow future researchers on adherence by parents of individuals with ASD to insert strategies in their research to favor adherence and monitor their effectiveness in doing so, as well as to evaluate how adherence rates can contribute to the results found